Heterosis in rice crosses involving IR68897A CMS line under mid-hill conditions of Himachal Pradesh - Kaur, Parwinder; Pandey, Deo Prakash (Journal of Cereal Research, 2019)
To increase the rice production, it is essential to improve rice yield because there will be little scope in further expanding the rice area Hybrid rice is one of such innovation. A field experiment was conducted during kharif 2016 with 10 hybrids generated by crossing ten male parents with CMS line IR68897A. The heterosis was estimated for yield and yield contributing characters. Considerable heterosis existed both in positive and negative directions for all the traits. The use of male sterility system (CMS) in developing hybrid rice is possible only when effective maintainers and restores are identified. Out of 10 crosses evaluated 2 restorers (IR 68897A x Ranbir Basmati and IR 68897A x HPU 741), 7 partial restorers and 1 maintainer (IR 68897A x T23). Heterosis expressed as per cent increase or decrease in the mean values of F1 hybrid over better parent and standard check were observed for various characters. IR68897A × HPR 2880, IR68897A × Ranbir Basmati, IR68897A × HPU 741 showed significant positive heterosis for grain yield over better parent. DOI: https://doi.org/10.25174/2249-4065/2019/95199